Construction of a Subject thesaurus to Śaivāgamas – Special reference to Agnikārya vidhi patala of Pūrva Kāmikāgama - Navaneethakrishnan, S. (Department of Hindu Civilization University of Jaffna, 2016)
The Śaivāgamas are regarded as authoritative and sacred by the Saivas of all schools. But unfortunately they have received much less attention from scholars even though their extent is remarkable. There are thesauri for popular sacred literature like Rigveda, Quran and Bible. The main objective of this paper is to construct a Subject thesaurus to Saivāgamas specially focused to Agnikārya vidhi patala of Pūrva Kāmikagama for depth understanding and optimum level of usage for the readers and researchers. This Thesaurus was constructed in Sanskrit and collection of terms selected from standard āgamic text. Each term and its semantic relationship with other terms were analyzed and displayed. More research studies are expected in Saivāgamās not only from Hindu research scholars but also from other religionists and Western scholar. This study would therefore serve a felt need by the Hindus and non-Hindus and place the Agamas before a world view.
Keywords: Saivagamas; Information retrieval; Vocabulary control device